(3cJGH UjO GdNGWQ ef efMI GdaGWQs ((3HgfGe GdeYQha HGdeJWHH s)
(3ChdgG (B:s
(3GdMeO ddg HGQF GdfSe heMi GdQee hHYO deG cfJ bO JWdYJ Ydi TF ef Yde GdWH GdPi dG ZfGA HGdfGS Yfg ai cd hbJ hReGf s
(3BNQgG (B:s
(3ajeG jWQO GdghGe JfMjO bQf GdCHd jWQO GdMjGJ hcPdc CXdGa GdYR hGdcHQjJ GdbWQGf Je GdcJGH hGdMeO ddg s
(3Cda GdeDda gPG GdcJGH ddSdWGf GdeXaQ GdefUhQ GdeLGgOs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs